Gembira bermain dengan biologi : 101 percobaan yang pasti berhasol / Janice Pratt Van Cleave ; penerjemah, Rifky Karim ; editor, Anni Yuliani - VAN CLEAVE, Janice Pratt; KARIM, Rifky; YULIANI, Anni (Pustaka Utama Grafiti, 1991)
xxv, 250 hlm : ilus ; 21 cm